1986
DOI: 10.1038/321864a0
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine impairs and β-carboline enhances performance in learning and memory tasks

Abstract: Benzodiazepines are widely used anxiolytics and anticonvulsants, and their potent sedative properties are routinely used in presurgical anaesthesia. However, they are also known to induce a strong anterograde amnesia in patients. Specific benzodiazepine antagonists have recently been described, some of which have intrinsic pharmacological properties that are opposite to those of benzodiazepines. These have been called inverse agonists and they have been shown to be proconvulsant or convulsant whereas benzodiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
1
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(200 citation statements)
references
References 16 publications
7
190
1
2
Order By: Relevance
“…Time at which mice enter the dark box, was noted and subsequently, the medians with 25 and 75 percentiles were calculated. The step-through, dark-light passive avoidance task gives information about acquisition (learning), consolidation, and retrieval; therefore, may be regarded as a measure of long-term memory (Venault et al, 1986). The influence of AEDs administered alone or in combinations on long-term memory was evaluated in three variants as follows:…”
Section: Chimney Testmentioning
confidence: 99%
“…Time at which mice enter the dark box, was noted and subsequently, the medians with 25 and 75 percentiles were calculated. The step-through, dark-light passive avoidance task gives information about acquisition (learning), consolidation, and retrieval; therefore, may be regarded as a measure of long-term memory (Venault et al, 1986). The influence of AEDs administered alone or in combinations on long-term memory was evaluated in three variants as follows:…”
Section: Chimney Testmentioning
confidence: 99%
“…Previous findings showed that allosteric modulators of g-amino butyric acid-A (GABA-A) receptors such as BDZ agents (positive modulators) or inverse agonist (negative modulators) of BDZ sites are effective in affecting these processes. BDZ compounds induce anxiolysis, sedation, and muscle relaxation (Thiebot, 1985;Venault et al, 1986;McNamara and Skelton, 1991;McNamara et al, 1993) and, under certain conditions, produce amnesia. Data derived from humans (Beracochea, 2006) and from laboratory animals have all shown that BDZ agents can impair memory.…”
Section: Introductionmentioning
confidence: 99%
“…The test was performed as described by Venault et al (1986). The apparatus consisted of a two-compartment chamber with an illuminated box (10 Â 13 Â 15 cm) connected to a large darkened box (25 Â 20 Â 15) by a guillotine door.…”
Section: Light-dark Step-through Passive Avoidance Taskmentioning
confidence: 99%
“…Time at which the mice entered the dark box was noted and subsequently, the medians with 25 and 75 percentiles were calculated. The step-through passive avoidance task gives information about ability to acquire the task (learning) and to recall the task (retrieval); therefore, may be regarded as a measure of long-term memory (Venault et al, 1986). The animals were administered with AEDs either singly or in combinations on the first day before training.…”
Section: Light-dark Step-through Passive Avoidance Taskmentioning
confidence: 99%
See 1 more Smart Citation